Notions of stinking oceans? models for organic carbon burial during cretaceous "anoxic events" - Arthur, Michael A.; American Association of Petroleum Geologists; Science-Thru-Media, Inc. (New York : Science-Thru-Media, Inc., 1984)
Organic carbon in sediments occurs in areas where it accumulates faster than it is decomposed chemically.
Slides mounted in 1 carousel.
"Sponsored by the American Association of Petroleum Geologists."
"A 1984 distinguished lecture."
Keywords: Sediments (Geology); Oceanography; Shale